Dexrazoxane added to doxorubicin-based adjuvant chemotherapy of breast cancer: a retrospective cohort study with a comparative analysis of toxicity and survival. Issue 7 (August 2017) - Tahover, Esther; Segal, Amiel; Isacson, Rut; Rosengarten, Ora; Grenader, Tal; Gips, Maya; Cherny, Nathan; Heching, Norman I.; Mesika, Lior; Catane, Raphael; Gabizon, Alberto
Abstract : Dexrazoxane is indicated as a cardioprotective agent for patients receiving doxorubicin who are at increased risk for cardiotoxicity. Concerns have been raised on the use of dexrazoxane, particularly in adjuvant therapy, because of the risk of interference with the antitumor effect of doxorubicin. Two meta-analyses in metastatic breast cancer have rejected this hypothesis, but have shown an apparent increase in the severity of myelosuppression when dexrazoxane is used. Here, we analyzed retrospectively a cohort of our institute database to assess whether the addition of dexrazoxane causes more bone marrow suppression in breast cancer patients receiving doxorubicin-based adjuvant therapy. The secondary objectives were assessment of the incidence of febrile neutropenia, dose-schedule modifications, recorded cardiac events or cardiac test abnormalities, and overall survival. Eight hundred and twenty-two female patients who received adjuvant (or neoadjuvant) doxorubicin and cyclophosphamide for breast cancer between 2001 and 2013 were included. One hundred and four of these patients also received dexrazoxane concurrently with the adjuvant treatment. Hospital records and, when accessible, community clinic records were reviewed. The median follow-up duration was 7 years for patients receiving dexrazoxane and 7.5 years for patients not receiving dexrazoxane. 85.6% of patients were alive at data lock. Compared with the nondexrazoxane group, patients who received dexrazoxane were older (median age at diagnosis 59 vs. 52 years) and more likely to receive dose-dense AC therapy (73 vs. 59%) and adjuvant trastuzumab treatment (29 vs. 15%). Compared with the nondexrazoxane group, dexrazoxane treatment was associated with a higher rate of hematological side effects: leukopenia (48 vs. 39%), neutropenia (45 vs. 31%, P =0.003), anemia (86 vs. 73%, P =0.005), and thrombocytopenia (37 vs. 22%, P =0.001). There were more febrile neutropenia hospitalizations (20 vs. 10%, P =0.001) and dose reductions (22 vs. 8%, P <0.001) in the dexrazoxane group, but no significant difference in the incidence of treatment delays or cancellations. The incidence of cardiac events was the same in both treatment groups with and without dexrazoxane. There was a nonsignificantly lower mortality rate in the dexrazoxane group (9.6%) compared with the nondexrazoxane group (15.0%) at data lock. Adding dexrazoxane to doxorubicin in adjuvant therapy patients leads to higher rates of bone marrow suppression in all blood components, as well as more febrile neutropenia events, and dose reductions. No differences in events defined as cardiac toxicities were detected. Dexrazoxane had no detrimental effect on survival, despite the higher hematological toxicity, the older median age, and the higher prevalence of HER2-positive disease in the dexrazoxane group.